A national survey of physicians regarding active surveillance for low-risk thyroid cancer in Korea - Min Joo Kim; Jae Hoon Moon; Eun Kyung Lee; Young Shin Song; Kyong Yeun Jung; Ji Ye Lee; Ji-hoon Kim; Woojin Lim; Kyungsik Kim; Sue K. Park; Young Joo Park (European Thyroid Journal)
Objective: Active surveillance (AS) has emerged as a viable alternative to immediate surgery for low-risk thyroid cancer. However, several barriers still hinder its widespread adoption and implementation by physicians. Methods: In 2024, an email survey was conducted among members of the Korea Thyroid Association to assess their perspectives on AS. The survey comprised questions about clinical case scenarios, perceptions of the benefits and risks associated with AS, factors influencing the consideration of AS and unmet needs for the implementation of AS. Results: Among the 287 physicians surveyed, 40.8% were endocrinologists, followed by general surgeons at 20.9% and otolaryngologists at 19.9%. The majority worked in tertiary hospitals and had over 10 years of experience. Regarding a 65-year-old man with a 0.7 cm low-risk thyroid cancer, 74.6% of the respondents considered AS. Endocrinologists and physicians with higher self-assessment and experience explaining AS to patients were more inclined to consider AS. Although the respondents recognized the benefits of AS, such as avoiding surgery and reducing surgical complications, they expressed concerns about potential risks, including the possibility of patient lawsuits due to disease progression and patient worry and anxiety about the disease. Challenges in screening candidates for AS were highlighted, especially in detecting recurrent laryngeal nerve involvement and lymph node metastases. Additionally, physicians noted unmet needs in AS implementation, specifically regarding psychological support for patients and reimbursement for long-term follow-up costs. Conclusions: The survey underscored the need for further research and initiatives to overcome the barriers and implement AS for the management of low-risk thyroid cancer.